(untitled) (World Bulletin of Public Health, 2026)
Mandibular fractures in children remain one of the most significant problems in pediatric maxillofacial surgery due to the increasing incidence of maxillofacial trauma and the high risk of long-term functional and morphological sequelae. Anatomical and physiological characteristics of pediatric bone tissue contribute to an atypical clinical course of fractures, which complicates timely diagnosis and increases the likelihood of complications, including disturbances in mandibular growth, occlusal deformities, and temporomandibular joint pathology. Despite the availability of clinical guidelines, issues related to the early detection of mandibular fractures in children and the prevention of their long-term consequences remain insufficiently systematized. In this context, synthesizing current evidence on the clinical and diagnostic features of mandibular fractures in children represents a relevant scientific and practical task.